2004
DOI: 10.1074/jbc.m313534200
|View full text |Cite
|
Sign up to set email alerts
|

A Loss of Viral Replicative Capacity Correlates with Altered DNA Polymerization Kinetics by the Human Immunodeficiency Virus Reverse Transcriptase Bearing the K65R and L74V Dideoxynucleoside Resistance Substitutions

Abstract: Mechanisms governing viral replicative capacity are poorly understood at the biochemical level. Human immunodeficiency virus, type 1 reverse transcriptase (HIV-1 RT) K65R or L74V substitutions confer viral resistance to 2,3-dideoxyinosine (ddI) in vivo. The two substitutions never occur together, and L74V is frequently found in patients receiving ddI, while K65R is not. Here we show that recombinant viruses carrying K65R and K65R/L74V display the same resistance level to ddI (about 9.5-fold) relative to wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 42 publications
(43 reference statements)
6
58
1
Order By: Relevance
“…For example, the M184V and V75T mutations in HIV-1 RT increase the NRTI-TP K d without significantly impacting the k pol (9,10,26). Other mutations, such as Q151M and L74V, decrease the k pol without affecting the K d (7,8). Consistent with prior reports, our data show that K65R predominantly exerts its discrimination effects by selectively decreasing the k pol (9,11,27), although small changes in K d were noted in this study and others (14,27).…”
Section: Discussionsupporting
confidence: 81%
“…For example, the M184V and V75T mutations in HIV-1 RT increase the NRTI-TP K d without significantly impacting the k pol (9,10,26). Other mutations, such as Q151M and L74V, decrease the k pol without affecting the K d (7,8). Consistent with prior reports, our data show that K65R predominantly exerts its discrimination effects by selectively decreasing the k pol (9,11,27), although small changes in K d were noted in this study and others (14,27).…”
Section: Discussionsupporting
confidence: 81%
“…The K65R mutation has been shown to use both mechanisms, depending on the NRTI-TP studied (Deval et al, 2004b;Deval et al, 2004a;White et al, 2005). We studied the binding/incorporation of apricitabine-TP for WT and relevant mutant RTs by determining the ratio of the inhibition constant (K i ) for apricitabine-TP to the K m for its natural counterpart dCTP.…”
Section: Resultsmentioning
confidence: 99%
“…The K65R mutation has been shown to decrease the binding or incorporation of zidovudine-TP as well as the k pol of tenofovir diphosphate compared with WT RT, with only a modest effect on K d (Deval et al, 2004a;White et al, 2005). Apricitabine-TP has been shown to inhibit HIV-1 WT RT with a K i that is twofold lower than that of lamivudine-TP in vitro .…”
mentioning
confidence: 99%
“…It has been shown that L74V in the context of the NL4-3 laboratory strain has an 11% loss of fitness compared to that of the wild type or K70R (154). Biochemical studies have shown that this replication decrease is associated with a reduction in the incorporation of nucleotides compared to the wild type and a decrease in the initiation of minus-strand and plus-strand DNA synthesis from the tRNA 3 Lys and polypurine tract primers (47,49). A reduced ability of L74V viruses to synthesize proviral DNA was demonstrated in cell culture (61).…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 98%
“…L74V and K65R, which are rarely found together in clinical isolates, have markedly antagonistic effects on viral fitness that correlate with reductions in the ability to utilize normal nucleotides during DNA synthesis (47). Similarly, K65R and M184V also have antagonistic effects on fitness that are associated with abnormalities in nucleotide incorporation (46).…”
Section: Mutational Interactions That Affect Fitness Intragenic Intermentioning
confidence: 99%